2014
DOI: 10.1016/j.oooo.2014.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Chemoprevention of oral cancer by topical application of black raspberries on high at-risk mucosa

Abstract: Objective To evaluate the preclinical efficacy of topical administration of freeze-dried black raspberries (BRBs) to inhibit the progression of premalignant oral lesions and modulate biomarkers of cancer development in high at-risk mucosa (HARM). Study Design Hamster cheek pouches (HCPs) were treated with carcinogen for six weeks to initiate a HARM microenvironment. Subsequently, right HCPs were topically administered a BRB suspension in short-term or long-term studies. After 12 weeks, SCC multiplicity, SCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 38 publications
0
28
0
1
Order By: Relevance
“…Previous researches have revealed that several kinds of animals can be used to establish OSCC models, including hamsters, rats, mice, dogs, and cats (12)(13)(14)(15)(16)(17). As early as 1954, squamous cell carcinoma (SCC) of the cheek was induced in hamsters by 9,10-dimethyl-1,2-benzanthracene (DMBA), and hamster SCC exhibits many similarities to human OSCC, including the morphology, histology, infiltration and metastasis, expression of biomarkers, and genetic and epigenetic alterations (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches have revealed that several kinds of animals can be used to establish OSCC models, including hamsters, rats, mice, dogs, and cats (12)(13)(14)(15)(16)(17). As early as 1954, squamous cell carcinoma (SCC) of the cheek was induced in hamsters by 9,10-dimethyl-1,2-benzanthracene (DMBA), and hamster SCC exhibits many similarities to human OSCC, including the morphology, histology, infiltration and metastasis, expression of biomarkers, and genetic and epigenetic alterations (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Several natural compounds and micronutrients (green tea extract, curcumin, resveratrol, broccoli sprout extract, soybean extracts, vitamin E, vitamin C, lyophilized black raspberries and pomegranate juice) have been under investigation for their adequacy in oral cancer chemoprevention (6,7). These compounds contain high levels of polyphenols with anti-oxidant, anti-migratory, antiproliferative and anti-invasive effects on cancer cell properties and are proposed to restrain carcinogenesis through their action on downstream signaling pathways (8).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we have mainly focused our attention on recent studies reporting novel targeting HNSCC/OSCC chemoprevention directed at interfering with the commonly deregulated oncogenic EGFR, PI3K, and mTOR pathways either by using selective drugs or common drugs marketed for other chronic conditions (i.e., celecoxib; metformin). Likewise, with the goal of reducing oral carcinogenesis, other novel chemopreventive strategies involving the systemic or topical delivery of natural products like green tea, grape seed extract, freeze-dried raspberries, and strawberries have been also used in high at-risk oral mucosa [77][78][79][80]. An important multidisciplinary area that deserves more attention is associated with the emerging developments in the field of nanochemoprevention.…”
Section: Discussionmentioning
confidence: 99%
“…Following a 12-week study, the authors observed that in comparison to controls, the freeze-dried black raspberry-treated group had reduced tumor multiplicity (~41 %), tumor incidence (~37 %), and tumor cell proliferation rate (~7 %) [78]. Likewise, the same research group studying oral carcinogenesis in a similar animal model demonstrated that lyophilized strawberries present in the diet may trigger positive effects on the chemoprevention of oral cancer.…”
Section: Natural Compounds As Chemopreventive Agentsmentioning
confidence: 96%